Deradicalization Education with a Feminist Perspective: Opportunities and Challenges - Suliantoro, Bernadus Wibowo; Runggandini, Caritas Woro Murdiati (SEAN Institute, 2024)
The spread of radicalism took place massively in the community, but unfortunately education model of gender-sensitive deradicalisation does not exist yet. The aim of the study is to find an education model of deradicalisation by utilizing femininity values to erode, brake, counteract, and prevent the development of radicalism. The research model is conducted by combining field research with library research. The collected data are analyzed qualitatively by using elements of philosophical methods in the form of: interpretation, internal coherence, holistics, historical continuity and heuristics. The results of the study found: 1) Deradicalization is essentially an attempt to revive maternal values towards those parties who are influenced by radicalism. Femininity values in the form of love, respect for life, inclusive, tolerance, cooperation, interconnection and interdependence with one another, empathy, care, and equality need to be promoted to prevent the development of radicalism. 2) Women need to be involved in the process of delivering deradicalisation messages because they are more persuasive, more patient, and smarter in touching the feelings of those who have been influenced by radicalism. Women also have an important role to arouse the femininity of women's radicalism groups to revive femininity values. 3) Women-friendly public spaces are needed for convicts who have undergone the process of deradicalization, so that they do not rejoin their groups as well as prevent the development of religious radicalism.